MATHEMATICAL MIND MAPPING ABILITY OF SENIOR HIGH SCHOOL STUDENTS IN PALEMBANG CITY: South Sumatera, Indonesia - Ummu Na’imah; Istiqomah; Bonita Hirza; Dyah Febriyana (Universitas Muhammadiyah Bengkulu, 2026)
Mind mapping is considered an effective visualization strategy for improving conceptual understanding in mathematics. However, little is known about students' ability to construct mathematical mind maps. This study aimed to describe the mathematical mind-mapping ability of senior high school students in Palembang City. A descriptive quantitative design was employed by using voluntary/convenience sampling, 90 senior high school students from public and private schools in Palembang participated in the study. Data were collected through Google Forms using a mathematical mind-mapping task and assessed using a rubric adapted from Tony Buzan's mind-mapping criteria consisting of central image, branching structure, keywords, colours, images, and hierarchy. The rubric was reviewed by two mathematics education experts to establish content validity and scored independently. Of the 90 submitted mind maps, only 34 met the predefined assessment criteria and were included in the scoring analysis. The analysed 34 mind maps obtained an average score of 33.67, which falls into the poor category. The findings suggest that explicit instruction and continuous practice in mathematical mind mapping should be integrated into classroom learning. Keywords: ability, mind mapping, visualization, mathematics, Palembang